EFFECTS OF BASIC LIFE SUPPORT TRAINING ON THEKNOWLEDGE OF BACHELOR OF SCIENCE IN NURSING STUDENTS (Journal of Medical & Health Sciences Review, 2025)
Background Basic Life Support training significantly enhances the skills, confidence, and retention of nursing students in emergency response, especially when simulation-based and interactive learning methods are used. Research shows that this type of training increases CPR proficiency, and ensures long-term competency.Objective: To evaluate the impact of BLS training on the knowledge of bachelor of science in nursing students’ and how BLS training effects the practical application of nursing students in lifesaving activities.Method: A quasi-experimental study design with pretest, post immediate test and post test was conducted at Rashid Latif nursing college. Non-probability purposive sampling technique was used for the selection of 126 participants. The training included a power point presentation, hands on practice and video demonstration. Data were collected from the participants. Data analysis was performed via SPSS version 23 with Fredman’s ANOVA used for statistical analysis.Result: The findings show noteworthy improvement in BLS knowledge during assessment periods. During the pre-test, respondents were poor mean score (mean=48.9%), (mean=68.3%) average, and none good. Immediate post-test results indicated remarkable improvement, with good score (mean=96.5%) and poor (mean=28.55%). Knowledge retention continued to be excellent at one-month follow-up showing good scores (mean=91.6%) and poor scorers reducing to (mean=23.8%) with average scorers rising to (mean=81.0%). Results suggest that BLS training succeeds in enhancing as well as retaining knowledge among nursing students.Conclusion: After the training there was a significant effect on the knowledge of BS nursing students. However, there was a noticeable decrease in knowledge retention with time.